2022
DOI: 10.3389/fsufs.2022.1017398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of jasmonic acid elicitation on composition of pigments and biological activities in green callus of neem (Azadirachta indica)

Abstract: This study was carried out with the aim of determining the effects of jasmonic acid (JA) elicitation on the bioactive pigments' biosynthesis and the antioxidant activities in green callus of Azadirachta indica of two different ages (4- and 8-week-old). Plant tissue culture technique was employed to induce the formation of green callus from leaf explants of A. indica on Murashige and Skoog (MS) medium supplemented with 0.6 mg/L thidiazuron (CM) and three different concentrations of JA (2, 4, and 6 mg/L). The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…32 Additionally, the exogenous application of JA and its derivatives to plants elicits a defense response that releases secondary metabolites with insecticidal properties, such as coumarin, vanillic acid, nicotine, and terpenoids. 20,21 From a pest control standpoint, phytohormones can partially alleviate pest-related harm and enhance plant resistance to herbivores while concurrently diminishing the ecological and human health consequences of chemical pesticide use, thereby introducing a novel approach to integrated pest management. 19,33,34 Conversely, from an economic perspective, JA can stimulate the production of advantageous secondary metabolites in plants, including transcriptional regulation of downstream genes in medicinal plants to generate drug components.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 Additionally, the exogenous application of JA and its derivatives to plants elicits a defense response that releases secondary metabolites with insecticidal properties, such as coumarin, vanillic acid, nicotine, and terpenoids. 20,21 From a pest control standpoint, phytohormones can partially alleviate pest-related harm and enhance plant resistance to herbivores while concurrently diminishing the ecological and human health consequences of chemical pesticide use, thereby introducing a novel approach to integrated pest management. 19,33,34 Conversely, from an economic perspective, JA can stimulate the production of advantageous secondary metabolites in plants, including transcriptional regulation of downstream genes in medicinal plants to generate drug components.…”
Section: Discussionmentioning
confidence: 99%
“…JA can enhance plant resistance against arthropods, pathogens, and plant diseases, thereby offering a novel perspective on the relationship and function of JA in the interaction between plants and herbivores . Additionally, the exogenous application of JA and its derivatives to plants elicits a defense response that releases secondary metabolites with insecticidal properties, such as coumarin, vanillic acid, nicotine, and terpenoids. , From a pest control standpoint, phytohormones can partially alleviate pest-related harm and enhance plant resistance to herbivores while concurrently diminishing the ecological and human health consequences of chemical pesticide use, thereby introducing a novel approach to integrated pest management. ,, Conversely, from an economic perspective, JA can stimulate the production of advantageous secondary metabolites in plants, including transcriptional regulation of downstream genes in medicinal plants to generate drug components . Our findings indicate that mite infestation increases the JA content in the eggplant as well as an elevation in coumarin levels following mite infestation and exogenous JA application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahmad Fauzi etal. [ 44 ] reported that callus formation of Azadirachta indica that contained green pigment had higher bioactive pigment content and antioxidant potential activities compared with brown and cream callus, with TPC and TFC more highly correlated with FRAP than DPPH and ABTS radical scavenging activity. Thus, phenolic and flavonoid compounds of R. nasutus could be major factors in the FRAP assay.…”
Section: Discussionmentioning
confidence: 99%